Colloidal FeIII, MnIII, CoIII, and CuII Hydroxides Stabilized by Starch as Catalysts of Water Oxidation Reaction with One Electron Oxidant Ru(bpy)33+. Issue 3 (4th January 2019) - Chikunov, Andrei S.; Taran, Oxana P.; Pyshnaya, Inna A.; Parmon, Valentin N.
Abstract: Colloidal catalysts for oxidation of water to dioxygen, which are stable on storage and under the reaction conditions, are synthesized based on Co III, Mn III, Fe III and Cu II hydroxides. Stabilization of the colloids with dextrated starch allows the process of hydroxide ageing to be stopped at the stage of the formation of primary nuclei (ca. 2–3 nm from transmission electron microscopy data). Molecular mechanics and dynamic light scattering studies indicate a core‐shell type structure of the catalysts, where the hydroxide core is stabilized by the molecular starch network (ca. 5–7 nm). The colloidal catalysts are highly efficient in oxidizing water with one electron oxidant Ru(bpy)3 3+ at pH 7 to 10. The influence of pH, catalyst concentration, and buffer nature on the oxygen yield is studied. The maximal yields are 72, 53, and 78 % over Fe‐, Mn‐ and Co‐containing catalysts, respectively, and turnover numbers are 7.8; 54 and 360, respectively. The Cu‐containing catalyst is poorly effective to the water oxidation (the maximal yield is 28 % O2 ). The synthesized catalysts are of interest for stopped‐flow kinetic studies of the mechanism of the water oxidation and as precursors for anchoring nanosized hydroxides onto various supports in order to develop biomimetic systems for artificial photosynthesis. Abstract : Stability for oxidation : Stabilization of primary nuclei products of Fe III, Mn III, Co III salts hydrolysis using dextrated starch result in formation of an effective catalysts of water oxidation reaction at weakly basic pH (7.0–10.0) with high selectivity (72, 53, and 78 %) in presence of one—electron oxidant Ru(bpy)3 3+ .